Pemberdayaan Ekonomi Pedesaan: Analisis dan Solusi - M. Harry Mulya Zein; Sisca Septiani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2020)
This study aims to analyze the dynamics of the rural economy in Sukajaya Village, a newly formed village from expansion. Through a qualitative approach, this study examines strengths, weaknesses, opportunities, and threats in the agricultural, MSME, and social sectors in Sukajaya Village. It was found that Sukajaya Village has advantages in agriculture and culinary MSMEs but faces challenges such as a lack of government support and understanding of the digital economy. This research also reveals social problems, especially in education. Proposed solutions include improving digital infrastructure, entrepreneurship education, and social interventions for schooling. This research provides important insights into rural economic empowerment that can help Sukajaya Village face challenges and seize opportunities.